TEACHING EFL SPEAKING SKILLS: A SELF-STUDY OF EFFECTIVE LESSON PLANNING AND DELIVERY - The, Hery Yanto (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
English as a Foreign Language (EFL) teachers will encounter challenges while instructing students from diverse backgrounds. They will overcome these challenges when they use strategically designed, well-conducted lessons that have the potential to enhance students' engagement and proficiency in communication greatly. This research studied the best practices in planning and delivering English-speaking lessons to EFL students in China and Indonesia, utilizing a self-analysis of the teaching practice approach. This study clarifies the principles underlying the inception of two speaking exercises, namely